Root and tuber crops in the Bahamas - Smith, Leon S.; Swann, Ghaly; Richardson, Kenneth (International Center for Tropical Agriculture, 1986)
The supply, availability, and characteristics of cultivated land, cropping systems, yields, socioeconomic profile of producers, production vol., costs, and constraints, and the marketing of root and tuber crops in the Bahamas are analyzed. The internal and external demand of fresh products and their limitations are also discussed. Finally, the government policies related to root crop production are given, and research, training, and development activities are indicated. (CIAT)